Keripik Jamur Sebagai Hilirisasi Produk dari Hasil Budidaya Jamur Tiram (Pleurotus ostreatus) di Desa Bojong Koneng, Sentul, Jawa Barat - Retno Lestari; Abinawanto Abinawanto; Sanya Khaerunnisa; Rabbil Pratama Aji; Diki Nurul Huda; Putra Mahanaim Tampubolon (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2021)
Oyster mushroom cultivation is one of the economic drivers of the Bojong Koneng Village community. Standard operating procedures have been developed through a research process and have been well implemented in carrying out the mushroom cultivation. The development of downstream products from oyster mushroom cultivation harvests that have been carried out has become the focus of community service activities as value added that can improve the economy of the people of Bojong Koneng Village. The product developed as a continuation of the cultivation program is mushroom chips which have a good taste, crunchy texture, and high protein content. Community service activities are carried out through counseling, focus group discussions, mushroom chip making practices, and monitoring. The impact of this activity is able to increase the knowledge and skills of the people of Bojong Koneng Village and it is hoped that it can increase the productivity of the village community for better welfare.